Strategi pemasaran pameran muzium: Kajian kes Muzium Kesenian Islam Malaysia / Muhamad Amirul Hafiz Zulkifli - Muhamad Amirul Hafiz , Zulkifli (2017)
This study is to examine the marketing strategies used by the management of the Malaysian Islamic Art Museum, Kuala Lumpur and assess the effectiveness of marketing strategies used to attract visitors to the Malaysian Islamic Art Museum, Kuala Lumpur. A qualitative approach has been used as well as an interview session has been conducted to get a comprehensive picture of the marketing strategy applied by the museum. The result of this research is to know the effectiveness of marketing strategies used by museums to reach the visitor's presence and to give a new breath to the museum which is now one of the tourism destinations in the world today. Through the 4Ps Mixed Marketing Theory detailing product, price, promotion and place, it finds a positive impact in achieving visitors to the museum. This is because, this theory provides the opportunity for museum management without distinguishing the broad and clear representation of departments of museum products exhibit exhibitions. At the same time, the continuation of this theoretical application in the marketing of museums has implications that are equivalent to the purpose of the museum being opened, which is dedicated to preserving, collecting, preserving and educating the general public on Islamic art. The sequence also found that this revamped marketing strategy not only captures visitors but also contributes to the museum in terms of accommodating financial financing through ticket price sales, and contributes to the country's economic growth through edu-tourism destinations.